Leaders of Reform Progressive Republicans in Kansas, 1900 -1916 - La Forte, Robert Sherman (University Press of Kansas, 1974)
In Leaders of Reform Robert Sherman La Forte examines the intricacies of shifting factions within the state majority party over a two decade period, from the BossBusters and political machines of the early 1900s through the formation of a new party behind Theodore Roosevelt in 1913. He discusses the motives, activities, accomplishments, and failures of the progressive Republicans. He provides excellent vignettes of major leaders such as William Allen White, Arthur Capper, Joseph L. Bristow, and Charles Curtis, as well as lesserknown characters such as Walter Roscoe Stubbs, Edward H. Hoch, and Cy Leland, Jr.In providing a detailed analysis of virtually all Kansas progressive Republican leaders during the era, La Forte has made a valuable contribution to both state and national political history.